Spastic Diplegia and the MRI - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The MRI findings in 34 children with spastic diplegia examined between 2 and 10 years of age are reported from the Seirei-Hamamatsu General Hospital, Mikatabara, Hammamatsu, Shizuoka; Nagoya City Medical School; and the National Rehabilitation Center for Disabled Children, Tokyo, Japan.